Enoch from Antiquity to the Middle Ages, Volume I: Sources from Judaism, Christianity, and Islam - Reeves, John C. (Oxford University Press USA - OSO, 2018)
This volume provides a comprehensive set of core references to '1 Enoch'. It shows that the rich afterlives of Enochic texts and traditions can be studied more thoroughly by scholars of Second Temple Judaism and early Christianity as well as by scholars of late antique and medieval religions.